LITERATUR REVIEW : PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN PHBS PADA ANAK SEKOLAH DASAR - Setiawan, Ronaldo Damar; Dwipayanti, Ni Made Utami (ARCHIVE OF COMMUNITY HEALTH; Vol 10 No 3 (2023): Desember 2023DO - 10.24843/ACH.2023.v10.i03.p14, 2023)
Clean and Healthy Living Behavior (PHBS) can also be interpreted as actions taken to maintain a healthy body and the cleanliness and health of a person for their well-being, which includes both physical and psychological aspects. Implementation of PHBS efforts to prevent the spread of infectious diseases, maintain personal hygiene, improve health status, improve poor personal hygiene, increase self-confidence, and create beauty changes in behavior as a result of the learning process are influenced by several factors, one of which is health education. Health education is an activity or effort to convey health messages to communities, groups, or individuals. It is hoped that with these messages, communities, groups, or individuals will be able to obtain better health knowledge and influence their behavior. This study used a research method in the form of a literature review. The database source used to collect literature comes from Google Scholar. The researcher conducted a research review using the experiment design. The results obtained were that 11 journals showed that the provision of health education had a good impact on increasing PHBS knowledge after being given intervention media, including Audiovisual/Video, Peer Educators, Games, and Picture Story Books. Keywords: Health Education, Knowledge, PHBS, Elementary School Children